Management of Construction Planning Process in Massive Underground Mining by Integrating Lps and Cit Through Action Research - Jarufe-Troncoso, J (American Society of Civil Engineers, 2025)
Currently, in massive underground mining (MUM) many processes lack standardized methodologies for effective resource and time management. One such area is construction planning, which involves multiple time horizons and complex interactions between variables and activities. In recent years, methodologies rooted in lean philosophies have been applied to improve process control and compliance in MUM, but they often face difficulties to address site-specific constraints and intertemporal dependencies. Inadequate management of these factors can lead to significant project delays, consequently affecting production milestones. To address this gap, this paper introduces a planning methodology based in a central management system called Last Planner System (LPS) and continuous improvement tools (CIT), aimed to generate an improvement in the reliability of the processes led by the planning area. Action research (AR) is applied to evaluate existing practices for similar projects, implement the methodology, reflect upon and analyze the results, and develop guidelines for the methodology s reproducibility. The project assessed is a MUM operation in its initial construction stage characterized by specific operational constraints and constant deviations to the programming. The proposed methodology advanced project commissioning by three months, enabling the completion of all activities scheduled in the master plan s milestones and promoting operational continuity. Performance metrics validate the methodology s effectiveness, with limitations and confounding factors discussed. The methodology offers several benefits to the organization, including a traceable master plan (MP), the collaborative planning of operational constraints, and a dynamic visual monitoring of key project metrics. © 2025 American Society of Civil Engineers.